The expression a single Trigonometric function
Let's express the expression in terms of a single trigonometric function or a power of a trigonometric function, we can simplify it as follows:
First, we can use the trigonometric identity: tan(x) = sin(x) / cos(x).
Now, we can simplify by canceling out common terms in the numerator and denominator:
Now, we can see that the sin(x) term in the numerator cancels out with the sin(x) term in the denominator, and the cos(x) term in the denominator cancels out with the cos(x) term in the numerator:
= 1
For more such questions on Trigonometric function
#SPJ3
Answer:
cos²x
Step-by-step explanation:
Using the trigonometric identity
• tanx = , then
=
= sinxcosx ×
cancel the sinx in the multiplier with the sin x on the denominator
= cos²x
Answer:
3.
Step-by-step explanation:
This is a geometric series so the sum is:
a1 * r^n - 1 / (r - 1)
= 1 * (2^101 -1) / (2-1)
= 2^101 - 1.
Find the remainder when 2^101 is divided by 7:
Note that 101 = 14*7 + 3 so
2^101 = 2^(7*14 + 3) = 2^3 * (2^14)^7 = 8 * (2^14)^7.
By Fermat's Little Theorem (2^14) ^ 7 = 2^14 mod 7 = 4^7 mod 7.
So 2^101 mod 7 = (8 * 4^7) mod 7
= (8 * 4) mod 7
= 32 mod 7
= 4 = the remainder when 2^101 is divided by 7.
So the remainder when 2^101- 1 is divided by 7 is 4 - 1 = 3..
A.
(4, 0)
B.
(0, 4)
C.
(–2, –3)
D.
(–3, –2)
A. Is not a difference of squares
B. Is a difference of squares: (y − 5)2
C. Is a difference of squares: (y + 5)(y − 5)
D. Is a difference of squares: (y + 5)2
Option: C is the correct answer.
C. Is a difference of squares: (y + 5)(y − 5).
We are given a polynomial expression in terms of the variable y as follows:
Now this expression could also be written as:
This means that the expression is a difference of squares.
Also, we know that:
Here,
Hence,